Mechanisms of action underlying virtual reality exposure treatment in spider phobia: pivotal role of within-session fear reduction - Roesmann, Kati; Leehr, Elisabeth J.; Böhnlein, Joscha; Gathmann, Bettina; Herrmann, Martin J.; Junghöfer, Markus; Schwarzmeier, Hanna; Seeger, Fabian R.; Siminski, Niklas; Straube, Thomas; Dannlowski, Udo; Lueken, Ulrike (Journal of anxiety disorders, 2023)
Although virtual-reality exposure treatment (VRET) for anxiety disorders is an efficient treatment option for specific phobia, mechanisms of action for immediate and sustained treatment response need to be elucidated. Towards this aim, core therapy process variables were assessed as predictors for short- and long-term VR treatment outcomes. In a bi-centric study, n = 186 patients with spider phobia completed a baseline-assessment, a one-session VRET, a post-therapy assessment, and a 6-month-follow-up assessment (ClinicalTrials.gov, ID: NCT03208400). Short- and long-term outcomes regarding self-reported symptoms in the spider phobia questionnaire (SPQ) and final patient-spider distance in the behavioral avoidance test (BAT) were predicted via logistic regression models with the corresponding baseline score, age, initial fear activation, within-session fear reduction and fear expectancy violation as predictors. To predict long-term remission status at 6-month-follow-up, dimensional short-term changes in the SPQ and BAT were additionally included. Higher within-session fear reductions predicted better treatment outcomes (long-term SPQ; short- and long-term BAT). Lower initial fear activation tended to be associated with better long-term outcomes (SPQ), while fear expectancy violation was not associated with any outcome measure. Short-term change in the SPQ predicted remission status. Findings highlight that in VRET for spider phobia, the experience of fear reduction is central for short- and long-term treatment success and should be focused by therapists.
Online verfügbar 14. Oktober 2023, Version des Artikels 23. Oktober 2023
Gesehen am 17.05.2024